The Moral Foundations of Impact Evaluation. Issue 3 (3rd July 2022) - Henderson, Heath
ABSTRACT: Impact evaluation has become increasingly central to evidence-based social policy, particularly in the field of international development. While the act of evaluation requires numerous ethical decisions (e.g. regarding the problems to investigate, the tools of investigation, and the interpretation of results), the normative framework for such decisions is generally implicit, undermining our ability to fully scrutinise the evidence base. I argue that the moral foundation of impact evaluation is best viewed as utilitarian in the sense that it meets the three elementary requirements of utilitarianism: welfarism, sum-ranking, and consequentialism. I further argue that the utilitarian approach is subject to a number of important limitations, including distributional indifference, the neglect of non-utility concerns, and an orientation toward subjective states. In light of these issues, I outline an alternative framework for impact evaluation that has its moral basis in the capabilities approach. I argue that capabilitarian impact evaluation not only addresses many of the issues associated with utilitarian methods, but can also be viewed as a more general approach to impact evaluation.